Impact of patient positioning on the efficacy and safety of doxycycline pleurodesis in malignant pleural effusion: a pilot randomized trial - Hieba Gamal Ezzelregal; Ahmed Mohamed Abdelsamad (BMC Pulmonary Medicine, 2026)
Abstract Background Chemical pleurodesis is a standard palliative intervention for recurrent malignant pleural effusion (MPE). Historically, patient rotation after sclerosant instillation was routine to ensure uniform drug distribution, but evidence supporting this practice remains conflicting. The study question was, does doxycycline pleurodesis without patient rotation demonstrate comparable efficacy and safety to the standard rotation protocol? Methods This pilot randomized trial included 40 patients with recurrent MPE eligible for pleurodesis. Patients were randomized (1:1) to either a Rotation group ( n = 20), which underwent a 2-h sequential rotation, or a Non-Rotation group ( n = 20), which remained supine. The primary outcome was pleurodesis success at 1 month, assessed by chest ultrasonography. The secondary outcome was the Pleural Adherence Score (PAS) to objectively assess drug distribution and pain assessment. Results The mean age was 56.5 years. Pleurodesis success rates were identical between the rotation and non-rotation groups 85% (17/20) vs. 85% (17/20); P > 0.99, though the confidence interval was wide (− 22.13% to 22.13%). Crucially, ultrasound-derived PAS scores at day 1 were high and comparable between groups (Mean 20.0 vs. 21.2; P = 0.33), confirming effective sclerosant distribution without rotation. There were no significant differences in pain scores, drainage duration, or complication rates between the two groups. Conclusion Omitting patient rotation during doxycycline pleurodesis for MPE demonstrated comparable 1-month efficacy in this pilot study, though larger trials are needed to establish definitive equivalence. These findings support a simplified non-rotation protocol to reduce patient burden. Trial registration The trial was retrospectively registered at ClinicalTrials.gov (Identifier: NCT07147270). ClinicalTrials.gov PRS: Home page (Modernized) published 08/29/2025.